Prognostic Impact of 1‐Year Changes in Creatinine‐ and Cystatin C‐Based Estimated Glomerular Filtration Rate After Stroke on 5‐Year Outcomes: Insights From the Third China National Stroke Registry - Yin Zhang; Yuesong Pan; Hongyi Yan; Xia Meng; Jinxi Lin; Mengxing Wang; Hao Li; Qin Xu; Pan Chen; Anxin Wang; Yilun Zhou; Yongjun Wang (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The impact of long‐term renal function change on stroke outcomes remains unclear. This study used the CNSR‐III (Third China National Stroke Registry) cohort to determine whether changes in estimated glomerular filtration rate based on creatinine and cystatin C (eGFRCr+CysC) during the first year post stroke were associated with 5‐year stroke outcomes. Methods and Results We included 4270 patients with centrally tested serum creatinine and cystatin C at admission and 1 year post admission and evaluated 5‐year follow‐up data. Patients were stratified into quintiles based on the 1‐year changes in eGFR. The primary outcomes included all‐cause mortality, stroke disability, and stroke recurrence. In patients with acute ischemic stroke, the mean baseline eGFRCr+CysC was 88.6±22.6 mL/min per 1.73 m2, which decreased by 5.6% to 83.6±20.7 mL/min per 1.73 m2 at 1 year. Compared with patients with relatively stable eGFRCr+CysC (Q3), those with decreased eGFRCr+CysC (Q1) exhibited significantly increased adjusted risk of death (hazard ratio [HR], 1.96 [95% CI, 1.27–3.04], P=0.003) and those with increased eGFRCr+CysC (Q5) exhibited borderline significance (HR, 1.51 [95% CI, 0.94–2.42], P=0.09), after adjusting for confounders, including baseline eGFRCr+CysC and albumin‐to‐creatinine ratio. Patients with a significant decrease (odds ratio [OR], 1.74 [95% CI, 1.25–2.42], P=0.001) or increase (OR, 1.51 [95% CI, 1.06–2.15], P=0.02) in eGFRCr+CysC also experienced a higher risk of disability. Conclusions Both the decline and increase in eGFRCr+CysC levels in the first year post stroke were independently associated with all‐cause mortality and stroke disability. These findings indicate that monitoring eGFRCr+CysC changes could be important for predicting long‐term outcomes and informing poststroke care strategies.